EVALUATING THE ACCURACY OF INTRAOPERATIVE FROZEN SECTIONS FOR MARGIN ASSESSMENT IN ORAL CANCER SURGERY: A STUDY FROM A TERTIARY CARE HOSPITAL - Pankaj Chauhan; Surabhi Pandey; Akanksha; Tanu Agrawal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Complete excision of malignant cells offers the best chance of cure in oral cancer, but microscopic tumor spread cannot be detected visually or by palpation. Hence, intraoperative frozen section analysis is commonly used to assess surgical margins, providing rapid diagnosis, margin evaluation, and guidance on malignancy status and lymph node dissection. OBJECTIVE: We aimed to evaluate the role of frozen section diagnosis as a guide in resection of surgical margins of oral cancer. MATERIAL AND METHOD: This retrospective study included 52 patients (264 margins) with oral carcinoma who underwent surgical resection at SRMS-IMS. Frozen sections were examined immediately for margins and later compared with hematoxylin and eosin-stained paraffin sections. Patients with prior oral cancer, previous treatments, or no positive histopathology were excluded. Margins were classified as positive (tumor present), close (between 1 - 5 mm) or negative (≥5 mm). RESULT:  Out of 52 samples received and with a total of 264 margins examined, the intraoperative frozen section demonstrated a sensitivity of approximately 79% and a specificity of about 98%. The positive predictive value was 86%, and the negative predictive value was 98%. CONCLUSION: In our evaluation, we concluded that frozen section is a valuable intraoperative tool with high specificity but moderate sensitivity. It aids in identifying positive margins, allowing timely revision during surgery.